Synthesis and Evaluation of Glycoconjugates Comprising N‐Acyl‐Modified Thomsen–Friedenreich Antigens as Anticancer Vaccines. (14th April 2016) - Sun, Shuang; Zheng, Xiu‐Jing; Huo, Chang‐Xin; Song, Chengcheng; Li, Qin; Ye, Xin‐Shan
Abstract: Thomsen–Friedenreich (TF) antigen is an important tumor‐associated carbohydrate antigen. Its low immunogenicity, however, limits its application in the development of anticancer vaccines. To solve this problem, several N ‐acyl‐modified TF derivatives were synthesized and conjugated with carrier protein CRM197 (a mutated diphtheria toxoid cross‐reactive material). The immunological results in BALB/c mice demonstrated that these modified TF antigen conjugates could stimulate the production of higher titers of IgG antibodies that cross‐reacted with native TF antigen. These glycoconjugates showed strong lymphocyte proliferative response, suggesting that they can induce cellular immunity. Furthermore, the elicited antisera reacted strongly with TF‐positive tumor cells (4T1). In particular, the N ‐monofluoroacetyl‐modified TF conjugate4 ‐CRM197 showed the strongest complement‐dependent cytotoxicity effect against 4T1 cells, implying the potential of this glycoconjugate as an anticancer vaccine. Abstract : Recruiting the IgG army : Several N‐modified TF antigen derivatives were synthesized and conjugated with the carrier protein CRM197. These glycoconjugates significantly increased the titers of antibodies than can recognize the native TF antigen and kill tumor cells, thus having the potential for use as carbohydrate‐based anticancer vaccines.